Perceived ability to comply with national COVID-19 mitigation strategies and their impact on household finances, food security, and mental well-being of medical and pharmacy students in Liberia. - Elvis J Davis; Gustavo Amorim; Bernice Dahn; Troy D Moon (PLoS ONE)
Introduction From the outset of the COVID-19 pandemic, guidance from WHO has promoted social distancing, wearing face masks, frequent hand washing, and staying-at-home as measures to prevent the spread of COVID-19. For many across Africa, compliance can be difficult. The aim of this study was to 1) understand the impact of student's household's ability to comply with COVID-19 mitigation strategies, 2) identify predictors of mitigation strategy compliance, and 3) describe the impact of COVID-19 on household economics, food-security, and mental well-being. Materials and methods We conducted an email-based survey among current medical and pharmacy students of the University of Liberia College of Health Sciences between July and October 2020. The questionnaire was designed to explore their household's ability to comply with current mitigation strategies, as well as the pandemic´s impact on the student's household's finances and food security. Descriptive statistics were used to delineate demographic characteristics. Logistic regression was used to model factors associated with ability to comply with COVID-19 mitigation strategies, as well as participant's food security. Results 113 persons responded to the questionnaire. Seventy-six (67∙3%) reported income losses as a result of the pandemic, with 93 (82∙3%) reporting being "somewhat" or "very worried" about their households' finances. Seventy-seven (68∙1%) participants reported food stocks that were sufficient for one-week or less. Forty (35%) participants reported eating less preferred foods or skipping meals in the past week. Overall, 20 participants (19∙4%) had a positive depression screen. Conclusions Study participants showed mixed results in being able to adhere to national COVID-19 mitigation strategies, with household level stressors experienced around finances and food security. Until Liberia has access to vaccinations for most of its citizens, COVID-19 response measures need to provide social protections that address basic needs (shelter, clothing and food), and which specifically targets food insecurity. Preventative interventions for mental health problems must be incorporated into Liberia's response to the pandemic.